A Heteroleptic Ferrous Complex with Mesoionic Bis(1, 2, 3‐triazol‐5‐ylidene) Ligands: Taming the MLCT Excited State of Iron(II). Issue 9 (11th December 2014) - Liu, Yizhu; Kjær, Kasper S.; Fredin, Lisa A.; Chábera, Pavel; Harlang, Tobias; Canton, Sophie E.; Lidin, Sven; Zhang, Jianxin; Lomoth, Reiner; Bergquist, Karl‐Erik; Persson, Petter; Wärnmark, Kenneth; et al.
Abstract Strongly σ‐donating N‐heterocyclic carbenes (NHCs) have revived research interest in the catalytic chemistry of iron, and are now also starting to bring the photochemistry and photophysics of this abundant element into a new era. In this work, a heteroleptic FeII complex (1) was synthesized based on sequentially furnishing the FeII center with the benchmark 2, 2′‐bipyridine (bpy) ligand and the more strongly σ‐donating mesoionic ligand, 4, 4′‐bis(1, 2, 3‐triazol‐5‐ylidene) (btz). Complex 1 was comprehensively characterized by electrochemistry, static and ultrafast spectroscopy, and quantum chemical calculations and compared to [Fe(bpy)3](PF6)2 and (TBA)2[Fe(bpy)(CN)4]. Heteroleptic complex 1 extends the absorption spectrum towards longer wavelengths compared to a previously synthesized homoleptic FeII NHC complex. The combination of the mesoionic nature of btz and the heteroleptic structure effectively destabilizes the metal‐centered (MC) states relative to the triplet metal‐to‐ligand charge transfer (3MLCT) state in 1, rendering it a lifetime of 13 ps, the longest to date of a photochemically stable FeII complex. Deactivation of the 3MLCT state is proposed to proceed via the 3MC state that strongly couples with the singlet ground state.